Faktor Yang Mempengaruhi Pemilihan Jenis Tanaman Di Areal Perhutanan Sosial Lembaga Masyarakat Desa Hutan Sasaka Patengan - Soni Trison; Anis Tri Rahayu; Tsanie Ditya Kurnia (Jurnal Hutan dan Masyarakat, 2024)
The development of the management of social forestry areas uses the approaches of agroforestry. Selecting the right plants to combine with this approach creates challenges in matching plant species to the environmental conditions where they will grow. This study aims to explore the factors considered by farmers when choosing plant species for cultivation. The research employs purposive sampling of three Social Forestry Business Groups (KUPS) that have received official decrees (SK) to manage social forestry. These groups situs slot777 terpercaya have implemented agroforestry approaches and combined various plant species. Data was collected through direct observation, interviews with respondents, and literature review. Socio-cultural, ecological, and economic factors significantly influence farmer’s decisions in selecting plant species for cultivation. The data indicates that economic factors account for 40%, ecological factors 33%, and socio-cultural factors 27% in choosing suitable plant species for cultivation